2018
DOI: 10.1111/ppc.12291
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge and attitudes about dementia care: Systematic literature review

Abstract: This review contributes to care advancement and practice development through the reinforcement of organizational support and educational opportunities for nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
101
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 43 publications
17
101
3
4
Order By: Relevance
“…Demographic change continuously leads to an increase in the number of patients with dementia in nursing homes for the elderly [ 12 ]. Dementia care can be very challenging due to the cognitive and functional decline of patients; however, it may be suggested that nurses’ low level of knowledge of patients’ needs and an unfavorable attitude towards dementia care can have a negative impact on care, patient safety, and symptom management [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Demographic change continuously leads to an increase in the number of patients with dementia in nursing homes for the elderly [ 12 ]. Dementia care can be very challenging due to the cognitive and functional decline of patients; however, it may be suggested that nurses’ low level of knowledge of patients’ needs and an unfavorable attitude towards dementia care can have a negative impact on care, patient safety, and symptom management [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surr et al [ 7 ] highlighted stigmatization or negative staff attitudes and limited staff skills or knowledge regarding dementia, besides negative culture in wards and institutions and unsupportive physical environments, as key causes behind poor outcomes in PwD admitted to hospitals. In their recent review, Evripidou et al [ 8 ] supported the assumption that acute care nurses’ attitude toward PwD is rather negative. It was also found that hospital staff might not be aware of the needs that older people have, because they lack specialized education and understanding [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that hospital staff might not be aware of the needs that older people have, because they lack specialized education and understanding [ 4 ]. However, a higher dementia knowledge level is supposed to correlate positively with positive attitudes [ 8 ] and, vice versa, there is evidence that shows a correlation between lack of knowledge and negative attitudes toward older people [ 9 ]. The latest World Alzheimer Report [ 10 ] titled “Attitudes to dementia”, highlights the importance of this topic in general.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults with dementia were excluded although they are able to send and receive nonverbal information [39]. Dementia care combines comorbidities, cognitive and functional decline; leading to complex needs and ever-increasing difficulty for the patient in articulating them (36). It is viewed as a challenging form of care.…”
Section: Conceptmentioning
confidence: 99%